Unpapered : Writers Consider Native American Identity and Cultural Belonging - Rodriguez, Linda; Glancy, Diane (Book collections on Project MUSE., 2023)
"Unpapered brings together personal narratives of Indigenous writers to explore the meaning and limits of Native American identity beyond its legal margins"--